Labour market in Asia and Europe: A comparative perspective on unemployment hysteresis - Furuoka, Fumitaka; Idris, Aida; Lim, Beatrice; Boroh, Rostika Petrus (AEI Insights, 2021)
The main problem of the European labour market is its high unemployment. By contrast, Asian countries do not face the high unemployment. In order to explain this differences, this paper aims to compare labour market outcomes, particularly unemployment rates, labour market institutions and unemployment protection mechanisms, in Asia and Europe. Despite numerous studies on this topic using econometric analysis, there is still lack of descriptive analysis of labour market in this important topic in the labour economics. Thus, this paper uses some descriptive statistics to explain the differences in the labour market between Asia and Europe. Results of secondary data analysis indicate that there is a remarkable difference in labour market outcomes between the two regions, especially in unemployment rates, where the rates for Asia are relatively lower than those for Europe. The main feature of Asian unemployment is that unemployment rates are quite stable, whereas for Europe they are persistently high. In Europe, unemployment rates tend to increase when a country faces an economic crisis and will reduce when the economy recovers from the crisis. However, the level of reduction often does not reach pre-crisis rates. This appears to be mainly due to provisions of the generous unemployment benefits in Europe, where policymakers often have to make a paradoxical balance between labour market flexibility and employment protection. By contrast, in Asian countries, unemployment rates do not seem to be affected by economic conditions. Some possible factors contributing to this trend include a weaker unemployment protection mechanism, a strong existence of an informal sector and a prevailing culture of self-help in the region. As a conclusion, Europe appears to face a greater problem with unemployment hysteresis while Asia’s the severity of the unemployment problem is less because the effect of economic crisis on unemployment tends to be smaller in Asia than in Europe.